Computer systems in medical practice. I. The aims, difficulties and implementation of computerization in health care organizations - Michalak, J (Medycyna pracy, 1995)
Several phenomena accompanying the implementation of computer systems in polish health care are discussed. The initiatives of managers of health care organizations or individual hospitals, are directed toward the software supporting their financial and administration activities. On the other hand, the Ministry of Health initiatives deals mainly with registration of manpower (doctors, nurses, etc.), and registration of equipment of health care organizations. Several computer programs elaborated by the polish authors are adjusted to the needs and abilities of health care organizations, hospital and private practices of individual doctors. However, the possibilities of data exchange between different computer software systems are rather limited. Implementation of computer systems are accompanied by the resistance resulting from the fears personnel which uses computers in the health care organizations. The effectiveness of computer systems implementation depends mainly on the user's ability to define precisely his needs, and on approval the computer system by the personnel.